Adoption Rate and Use Intensity of Bundled Climate Information Services and Climate-Smart Agricultural Technologies in Ethiopia - Tesfaye, Abonesh; Ambaw, Gebermedihin; Solomon, Dawit (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
This study aims to understand the adoption rate and use intensity of enhanced climate information services and climate-smart agriculture technologies in the Doyogena, Menz, Bekoji, and Digeluna Tijo districts in Ethiopia. A simple random sampling technique was employed to select 523 respondents from the four districts. Both descriptive and econometric methods were used to analyze the data. Descriptive statistics such as mean, frequency, and percentages were used to assess the rate and intensity of adoption of the improved technologies while the double-hurdle econometric model was employed to estimate determinants of the likelihood of adoption decision and use intensity of these technologies. Our findings revealed an adoption rate of 73%, 68%, and 18% for site-specific fertilizer recommendation, Climate-smart integrated small ruminant innovations (Smart Pack), and user-centric bundled digital climate agro advisories, respectively. The results further indicated that the education level of the respondents, farm household assets formation such as ownership of farmland and tropical livestock unit, the access road to marketplaces, and farmers group membership were the main determinants of the probability of adoption and use intensity of these technologies. This study highlights the importance of prioritizing and promoting asset building and accumulation among farm households, investing in developing farmers' training centers and infrastructure such as access roads, and encouraging and facilitating smallholder farmers to join farmers' groups and cooperatives. These may empower farm households to efficiently utilize improved agricultural technologies and advance the uptake and sustainability of these technologies, contributing to the enhanced welfare of smallholder farmers.